Metaverse and the Web 3: a systematic mapping - Coronado, Angelo; Berretta, Luciana de Oliveira; Carvalho, Sergio T. (Anais do Colóquio em Blockchain e Web Descentralizada (CBlockchain); 2023: Anais do I Colóquio em Blockchain e Web DescentralizadaDO - 10.5753/cblockchain.2023.229957, 2023)
The Metaverse and the Web 3 are two emerging technologies whose adoption is growing lately. More enterprises are investing in them to keep up with the market. Therefore, it is important to have a general and better understanding of Metaverse and the Web 3 also known as the decentralized web. This paper describes the relationship between these two technologies through a systematic mapping methodology, aiming to contribute to a clearer understanding of the Metaverse and Web 3.